Retrobulbar lymphoma associated with a ballistic foreign body in a cat. (20th August 2015) - Robat, C.; Bemelmans, I.; Marescaux, L.
Abstract : A seven‐year‐old domestic shorthair cat, adopted 5 years previously with a corneal perforation of the left eye, was presented for investigation of a left orbital mass. Computed tomography revealed a metallic foreign body within a contrast‐enhancing, heterogeneous orbital mass. Large cell lymphoma was diagnosed from a fine needle aspirate. The cat staged negatively and was treated with l‐asparaginase, prednisolone and three fractions of radiation therapy. A rapid clinical remission was obtained and the cat remained in remission for 3 years after therapy. This is the first report of large cell lymphoma likely occurring secondary to a foreign body.